Influency of hyperlipidemia in diabetics women (type II) - Martins, H. P. (1994)
Glycohemoglobin, glucose, lipids, alfa e beta globulins were measured in 46 woman type II diabetics. We investigated the influence on the plasma glucose in comparison with the concentration of total cholesterol, HDL cholesterol and triglycerides, avoid increase the risk of atherosc1erois in patients wich poor metabolic control. The correlation was positively between glucose levels in patients diabetics non insulin dependents and cholesterol, HDL-cholesterol and triglycerides and can suggest the hyperglycemic effect in the lipidic metabolism. The effect of diabetes on HDL levels is greater in women than in men and our study suggest 20% lower than in age and sex-matched non diabetics, and thisdecrease in HDL-cholesterol cannot be accounted for by obesity. This diabetics type II generally has little effect on total cholesterollevels with media of 243 mg/dl, also contribute to the observed excess in cardiovascular risk in diabetics. Even in those individuaIs without frank hyperlipidemia, increases in plasma  triglycerid levels are observed.